Find the integral surface of π₯2π + π¦2π + π§2 = 0 which passes through the curve x+y = xy, π§= 1.
x2p+y2q+z2=0
x2p+y2q=-z2
By lagrange equation;
"\\frac{dx}{x^{2}}=\\frac{dy}{y^{2}}=\\frac{dz}{-z^{2}}"
Taking the 1st and 2nd terms,
"\\frac{dx}{x^{2}}=\\frac{dy}{y^{2}}"
Integrate both sides,
"\\int \\frac{dx}{x^{2}}=\\int \\frac{dy}{y^{2}}"
"C_1+\\frac{1}{-x}=-\\frac{1}{y}"
"C_1=\\frac{1}{x}-\\frac{1}{y}" This is equation (i)
Taking the 2nd and 3rd terms,
"\\frac{dy}{y^{2}}=\\frac{dz}{-z^{2}}"
Integrate both sides
"\\int \\frac{dy}{y^{2}}=\\int \\frac{dz}{-z^{2}}"
"-\\frac{1}{y}+C_2=\\frac{1}{z}"
"C_2=\\frac{1}{y}+\\frac{1}{z}" This is equation (ii)
The equation of the curve given is x+y=xy and z=1
We let x=t
Therefore from the equation of the curve;
x=xy-y
Rearrange; xy-y=x
y(x-1)=x
"y=\\frac{x}{x-1}\\implies y=\\frac{t}{t-1}"
z=1
Put the above values of x,y and z in equations (i) and (ii) and remove t from the obtained relation
"C_1=\\frac{1}{t}-\\frac{t-1}{t}"
"C_1=\\frac{1}{t}-1+\\frac{1}{t}"
"C_1=\\frac{1}{t}+\\frac{1}{t}-1" This is equation (iii)
"C_2=1-\\frac{1}{t}+1"
"C_2=2-\\frac{1}{t}"
"\\frac{1}{t}=2-C_2" Replace this in equation (iii)
"C_1=2-C_2+2-C_2-1"
"C_1=3-2C_2" This is equation (iv)
Now replace the values of C1 and C2 in (iv) to get the required surface
"\\frac{1}{x}-\\frac{1}{y}=3-\\frac{2}{y}-\\frac{2}{z}"
"\\frac{y-x}{xy}=\\frac{3yz-2z-2y}{yz}"
"zy-xz=3xyz-2xz-2xy"
The Integral surface is;
"zy+xz+2xy=3xyz"
Comments
Leave a comment